Kalamezhuthu Pattu: A Linguistical Analysis Tracing The Cultural Values - et. al., Anjali Gopan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Language is intrinsic to the expression of culture. It is the channel through which culture and its traditions may be conveyed and preserved. The main goal of this paper is to inculcate the reciprocity of the Sapir-Whorf Hypothesis theory otherwise known as linguistic relativity with the traditional Indian ritual Kalamezhuthu Pattu celebrated in the temples of Kerala as these rituals play a vital role in enriching the cultural heritage of India. This theory claims that the structure of a language affects its speaker’s worldview or cognition and thus people’s perceptions are relative to their spoken language. This paper focuses on the symbols associated with the ritual and how these symbols contribute to the visual aesthetics of humans and how it helps in the cognition of linguistic and cultural connectivity. The authors also try to assay this ritual as a custom for ecological preservation which is in contrast to the current mechanized world.